EVALUASI PENERIMAAN SISTEM TNDE MENGGUNAKAN METODE TAM PADA PT ANGKASA PURA I BALI - ANAK AGUNG ISTRI WULAN PRAMIYANTI; I GUSTI LANANG SUTA ARTATANAYA; I MADE WIDIANTARA; COKORDA ISTRI SRI WIDHARI (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the effect of the variables Perceived Usefulness, Perceived Ease Of Use. Attitude Towards Using, and Actual Usage in the process of implementing the TNDE system at PT Angkasa Pura I I Gusti Ngurah Rai Bali International Airport Branch Office. The focus of this research is directed at the relationship of each variable with the indicator approach of each variable, so that the results are obtained as material for evaluating the system. The sample in this study was selected using a purposive sampling technique and a total of 89 people were obtained. The analysis technique used in this research is Partial Least Square Structural Equation Modeling (PLS-SEM) with analysis tools through the SmartPLS program. The results of this study indicate that all the hypotheses that have been formed and tested in the Technology Acceptance Model produce a positive and significant influence. This illustrates that the implementation of the system at PT Angkasa Pura I I Gusti Ngurah Rai Bali International Airport Branch Office is good.